Dynamic adsorption separation of c-C4F8/C3F8 for effective purification of perfluoropropane electronic gas. (5th June 2023) - Li, Xinxin; Yang, Cuiting; Du, Shengjun; Wu, Ying; Huang, Baolin; Tan, Aidong; Liang, Zhenxing; Xiao, Jing
Graphical abstract: Highlights: A series of adsorbents are evaluated for dynamic separation of c -C4 F8 and C3 F8 with high structure similarity for electronic special gas production. Carbonaceous GC-K1 showed superior dynamic c -C4 F8 /C3 F8 selectivity of 3.7 and uptake of 1.2 mmol/g for c -C4 F8 under ambient conditions. The impact of textural properties, particularly ultramicropore size of carbons activated by KOH on c -C4 F8 /C3 F8 separation is further discussed. The effective c -C4 F8 /C3 F8 separation is likely attributed to the stronger pore confinement effect of c -C4 F8 via the small ultramicropore (∼5.9 Å) in GC-K1. Abstract: The separation of c -C4 F8 /C3 F8 mixtures at ambient conditions is challenging in the electronic industry due to their similar physical and chemical properties. The object of this work is to explore effective adsorbents for c -C4 F8 /C3 F8 separation and elucidate its separation mechanism. Through screening a series of absorbents, KOH activated glucose-based carbon (GC-K1) stands out as the most effective adsorbent for the separation of c -C4 F8 /C3 F8 mixtures with the highest dynamic selectivity of 3.7 and adsorption uptake of 1.2 mmol/g for c -C4 F8, as well as multiple-cycle regenerability. The effects of textural properties, particularly the micropore size, on c -C4 F8 /C3 F8 separation were further investigated experimentally and computationally. The effective c -C4 F8 /C3 F8 separation over GC-K1 may be attributed to the discrepancy in the constrained adsorption affinity of c -C4 F8 over C3 F8 via the small ultramicropore at ∼5.9 Å. This study provides valuable insights into the adsorptive purification of electronic gases using ultramicroporous carbon via the pore confinement effect.